VAICTM PT. Astra Agro Lestari Tbk - Dara Angreka Soufyan; Yoga Nugroho; Devi Agustia; Cici Darmayanti; Said Mahdani; Thamitha Intassar Husen; Asraldi Barus (Universitas Teuku Umar, 2021)
The purpose of this study is to analyze the performance of the company through IC at the company PT. Agro Astra Lestari Tbk. This measurement uses the VAICTM model from 2017 to 2019. The data used in this study are secondary data in the form of financial reports which are presented on the official IDX website. The results of this study indicate that VAIC ™. Is increasing every year (2017-2019) and has succeeded in increasing the ability of BPI to become top perfomers based on BPI